HELPING STYLE IN THE PARENT–CHILD RELATIONS: BARRIERS AND FORMATION STRATEGIES - Shlat, Natalia; Pradun, Inna; Michailova, Arina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article analyzes the problem of child–parent relations as an important and in modern conditions the crisis component of a holistic family system. The authors consider various approaches to typifying the styles of family education of preschool children, specify the characteristic features of the relations between parents and children. The problem of child–parent relations in the modern family, according to the authors, finds its solution in educating the family according to the strategy of the "understanding parent", laid down in the concept of the helping style of the interaction between the child and parents.The article describes an empirical study of the features of interaction between a family and a preschool child: the diagnostic tools are characterized, the diagnostic procedure is described, and the results are analyzed. Based on the results of the experiment, the authors conclude that it is necessary to develop and implement the program «On the way to understanding parenting»: mission, content, forms of educational work with the family.The results of the study can be used as a basis for designing the content of pedagogical work on the organization of cooperation between a kindergarten and a family of pupils.